Negative thermophoresis of nanoparticles interacting with fluids through a purely-repulsive potential. (7th November 2017) - Tsuji, Tetsuro; Iseki, Hirotaka; Hanasaki, Itsuo; Kawano, Satoyuki
Abstract: Thermophoretic forces acting on nanoparticles are investigated using molecular dynamics simulation. We assume the Lennard-Jones (LJ) potential for the interaction between fluid molecules. On the other hand, the interaction between the nanoparticle and the surrounding fluid molecules are assumed to be either LJ or Weeks–Chandler–Andersen (WCA) potential, where the latter is purely-repulsive. The effect of the interaction potential on the thermophoretic force is investigated for various situations. It is found that the thermophoretic force basically acts in the direction from the hotter side to the colder side of the nanoparticle. However, when the surrounding fluid is in the liquid phase, the force acts in the reversed direction for the case of the WCA potential. It is clarified that the sign reversal is caused by the different structures observed in the distribution of repulsive forces acting on the nanoparticle.